Perencanaan Box Underpass Tunnel dengan Metode Kekuatan Batas (Ultimate Design): (Studi Kasus: Bundaran Besar, Kota Palangka Raya, Provinsi Kalimantan Tengah) - Kristianni Toendan; Fransisco Happy Riadi Haputra Baru; Maryanto Maryanto (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2026)
This study aims to design a Box Underpass Tunnel structure using the Ultimate Strength Design method to ensure structural safety, stability, and serviceability. The research applies a descriptive quantitative approach through technical analysis and structural calculations to evaluate the requirements and feasibility of a pedestrian underpass tunnel in the Bundaran Besar area, Palangka Raya City. The data utilized in this study consist of primary project data from the Menara and Bundaran Besar development obtained from the Public Works and Housing Agency of Central Kalimantan Province. The structural design uses K-300 quality concrete and U-41 reinforcing steel with a slab thickness of 45 cm. Structural modeling and analysis are performed using SAP2000 software to determine internal forces and reinforcement requirements. The analysis results show that the main reinforcement for the top slab is D19-50, wall slab is D19-150, and base slab is D19-50, while secondary reinforcement for all structural components uses D13-100. The findings confirm that the Ultimate Strength Design method provides an effective and reliable approach for designing Box Underpass Tunnel structures.